Investigation of Alphavirus of public health interest in equines in Foz do Iguaçu, the Triple Frontier region (Brazil-Paraguay-Argentina) - Alexander Welker Biondo; Tatiana Carneiro Rocha; Mario Antonio Navarro Silva; Thállitha Samih Wischral Jayme Vieira; Alexander Welker Biondo; Ivan Roque de Barros Filho; Robson Michael Delai; André de Souza Leandro; Beatriz Böger; Walfrido Kühl Svoboda; Eliane Carneiro (Revista de Ciência Veterinária e Saúde Pública, 2025)
Introduction: The Alphavirus genus encompasses arboviruses of great importance to public health. These viruses presents zoonotic potential and are associated with infections in humans and other vertebrates, including equines. Reverse transcription followed by polymerase chain reaction (RT-PCR) allows the early recognition of Alphavirus circulation, which is crucial for effective preventive measures adoption. This study aimed to investigate the presence of Alphavirus in equines hosts living in close contact with humans and other animals in the city of Foz do Iguaçu (Brazil), which is part of the Triple Frontier region of Brazil, Paraguay and Argentina.Methods: Equines serum samples (n=117) obtained in 2015 and 2016 were subjected to RT-PCR to screen for the presence of the viral genome.Results: All samples were negative for the presence of Alphavirus.Conclusions: These data indicate that the equines examined were not infected and did not represent a risk of viral transmission to humans or other animals during the period in which the samples were collected. This information is relevant because these animals may act as sentinels and urban disseminators of pathogens. Furthermore, active surveillance activities may also contribute to the reduction of negative impacts on the main economic activities of this region.